Desvelando identidades através de retalhos de histórias de vida: práticas de psicologia social - Teresinha Maria Gonçalves; José Ivo Follmann; Adriel Giordani Christ; Maria Bernadete Serafim Viola Prum; Lucas da Silva Ricken; Israel Souza da Silva; Greice Michels Tomazi (Ciências Sociais Unisinos)
The article proposes a reflection on identities based on empirical data collected from five life stories selected from the practice of Social Psychology II students at Universidade do Extremo Sul Catarinense (UNESC). Some common conceptions of identity are used, considering that identities can always be decomposed into several dimensions, such as the one called nuclear identity (ego identity), or the one that refers to the idea of human being as a being of project, or, still, the one that refers to the place and the territory. The analysis of life stories identifies scraps that help to unveil identities in permanent process. The article has a simple structure: a short introduction, a review of literature on three major pertinent conceptions, final remarks and suggestions for further research.